Nature of electrophilic oxygen: insights from periodic density functional theory investigations - Kenge, Nivedita; Pitale, Sameer; Joshi, Kavita (Surface Science, 2019)
Increasing demand of ethylene oxide and the cost of versatile chemical ethene has been a driving force for understanding mechanism of epoxidation to develop highly selective catalytic process. Direct epoxidation is a proposed mechanism which in theory provides 100% selectivity. A key aspect of this mechanism is an electrophilic oxygen (O-ele) species forming on the Ag surface. In the past two and half decades, large number of theoretical and experimental investigations have tried to elucidate formation of O-ele, on Ag surface with little success. Equipped with this rich literature on Ag-O interactions, we investigate the same using periodic DFT calculations to further understand how silver surface and oxygen interact with each other from a chemical standpoint. Based on energetics, Lowdin charges, topologies and pdos data described in this study, we scrutinize the established notions of O-ele. Our study provides no evidence in support of O-ele, being an atomic species nor a diatomic molecular species. In fact, a triatomic molecular species described in this work bears multiple signatures which are very convincing evidence for considering it as the most sought for electrophilic entity.
Keywords: Ag(100); DFT; Electrophilic; epoxidation; Nucleophilic oxygen

Role of facet in the competitive pathway of ethylene epoxidation - Nair, Aathira; Kenge, Nivedita; Joshi, Kavita (Surface Science, 2022)
Ethylene epoxide (EtO) is used as raw material for a broad range of products from pharmaceuticals and plastics to paints and adhesives. Although the reaction of ethylene interacting with preadsorbed oxygen on Ag surface is known for decades, the underlying mechanism of EtO formation is not completely understood. Successful investigation of oxametallacycle (OMC) intermediate common to selective as well as non-selective pathways has ensured at least 50% selectivity. The current study brings out the electronic signatures of distinct conformers of OMC stabilised on two different facets of Ag viz. (100) and (111). There are subtle differences between OMC conformers observed on these two facets with near-eclipsed on Ag(100) and near-staggered on Ag(111). A detailed analysis of Ag-O, C-O, C-C, and Ag-C interactions along with projected Density of States (pDOS) and projected Crystal Orbital Hamilton Population (pCOHP) imply towards ring closure on Ag(100) and hydrogen transfer on Ag(111). Finally, our understanding based on electronic and structural signatures are backed up by activation barriers computed through NEB calculations. Activation barrier for EtO is lower on (100) as compared to (111) facet. Thus, our study sheds light on how these differences between OMC affect the selectivity towards EtO.
Keywords: Ag(100); Ag(111); DFT; epoxidation; Ethylene Oxide (EtO); OMC

What leads to direct epoxidation? an exhaustive DFT investigation of electrophilic oxygen mediated epoxidation of ethylene on Ag(100) - Nair, Aathira; Joshi, Kavita (Computational Materials Science, 2024)
Extensive research has contributed to a better understanding of the commercially important epoxidation reaction. Selectivity, a crucial aspect of this reaction, has received significant attention in both experimental and theoretical investigations. However, a consensus regarding the role of electrophilic oxygen in epoxidation is yet to be reached. The present study is a theoretical examination of the prerequisites necessary for direct epoxidation to occur on the Ag(100) surface, at varied monolayer concentrations. Additionally, the study investigates the characteristics of various oxygen species interacting with ethylene to promote the direct epoxidation pathway. Based on the effective charges and projected density of states (pDOS) analysis, three oxygen variants were identified on the Ag(100) surface: atomic oxygen, dissociatively adsorbed molecular oxygen, and O 3 . The investigation reveals that all oxygen species, despite their physical and electronic differences, are electrophilic and undergo direct epoxidation. This work provides insights into the complex nature of epoxidation reaction and discusses electronic factors influencing the selective oxidation route on different Ag-O complexes.
Keywords: Ag(100); DFT; Direct epoxidation; Electrophilic oxygen; Ethylene Oxide (EtO); OMC